Anatomical Considerations for Clinical Predictability in Intraoral Defect Reconstruction: A Morphometric Study - Ferreira, Gabriely [UNESP]; Caldeira, François Isnaldo Dias [UNESP]; Dovigo, Lívia Nordi [UNESP]; Ribeiro, Eduardo Cotecchia; Bolini, Paulo Domingos André [UNESP]; Monnazzi, Marcelo Silva [UNESP] (FapUNIFESP (SciELO), 2024)
Objective: To analyze morphometric measurements in dry jaws, chins, and hip bones to contribute to clinical predictability in the reconstruction of grafted areas. Material and Methods: The sample comprised 619 anatomical specimens. Anatomical structures were measured at predetermined points using a digital vernier caliper. Measurements of average thickness and linear dimensions of the coronoid process, as well as the average thickness of the mentum and iliac crest points, were obtained. Results: The average morphometric measurements of anatomical structures revealed that male individuals exhibit larger values than female individuals, with a mean difference of 1.57 mm. The mean estimated bone volume of the iliac crest and iliac fossa was 21,347.19 mm³ and 21,125.56 mm³ for the left and right sides, respectively. The coronoid process displayed a smaller thickness (2.11 mm) and linear measurement (5.77 mm) in its upper portion and a larger thickness (3.63 mm) and linear measurement (14.51 mm) at its base, on average. In the mentum, the greatest average thickness was found at the midline, with a value of 12.90 mm. Conclusion: The surgeon can predict the amount of bone that can be obtained from donor areas, as well as the predominant type of bone in each area, aiming to optimize its clinical application. It is important to highlight that both the iliac crest and iliac fossa provide a significant bone volume in comparison to intraoral areas.
Keywords: Bone Transplantation; Dental Implants; Hip; Mandible; Therapeutics